Carbon black-silicate hybrid particle as well as preparation method and application thereof
By introducing silicate particles into carbon black production, carbon black-silicate hybrid particles are formed, the problem of uneven dispersion between carbon black and silicon-based fillers is solved, the mechanical properties of rubber materials are improved, and the environmental protection emission risks in carbon black production are reduced.
Patent Information
- Application Number
- CN202510082610.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing mechanical blending of carbon black and silicon-based fillers has the problem of uneven dispersion, which leads to the damage to the rubber performance and creates environmental protection emission risks during the carbon black production process.
By introducing silicate particles at the front end of carbon black production and manufacturing, carbon black-silicate hybrid particles are formed, and hybrid composite of micron or even nanoscale carbon-silicate particles is achieved, thereby obtaining highly dispersed carbon black-silicate hybrid particles.
High dispersion of carbon black-silicate hybrid particles is achieved, the mechanical properties of rubber materials are improved, and the existing carbon black production process is not changed, and the environmental pressure of exhaust gas treatment is not added, which reduces the cost of carbon black particles.
Smart Images

Figure CN119912828A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of production and preparation of carbon black, and in particular relates to a carbon black-silicate hybrid particle and a preparation method and application thereof. Background Art
[0002] Carbon black is an inorganic filler for rubber, which mainly plays a reinforcing role and is one of the key factors determining the final performance of rubber composite materials. However, pure carbon black has a high cost. Therefore, in order to reduce costs, the prior art usually mechanically blends carbon black with finished silicon-based fillers (such as silicon dioxide, kaolin, halloysite, etc.) to prepare composite materials. However, the composite material obtained by this method is unevenly dispersed in rubber, which will destroy the performance of rubber.
[0003] In response to the above problems, the prior art has proposed a method of introducing silicon-based particles at the carbon black production end. For example, patent CN202010945404.3 discloses a dual-phase carbon black production process. This solution mainly involves the reactor section of carbon black preparation, where silicon lattice powder is introduced through process water to generate C-Si dual-phase particles at high temperature. The structure of C-Si particles can be regulated by adjusting factors such as the flow rate of raw oil, process water flow rate, reactor cracking temperature, and flue gas residence time. However, the subsequent tail gas contains silicon elements, which has a certain impact on tail gas treatment, emissions, and even tail gas combustion heat transfer efficiency, and there are certain environmental emission risks for the existing traditional carbon black production process. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a carbon black-silicate hybrid particle and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing carbon black-silicate hybrid particles, comprising the following steps:
[0007] (1) feeding a carbon black structure inhibitor solution and crude oil into a reaction furnace for combustion and cracking reaction, and then cooling, filtering and crushing to obtain primary carbon black particles;
[0008] (2) mixing silicate and granulation water to obtain a silicate suspension; adding the obtained silicate suspension, the primary carbon black particles obtained in step (1) and the binder solution into a granulator for granulation to obtain the carbon black-silicate hybrid particles.
[0009] Technical principle:
[0010] The present invention introduces silicon-based particles at the front end of carbon black production to form hybrid particles in which silicon-based inorganic particles penetrate into the voids of carbon black aggregates or adsorb on the surface of carbon black, thereby achieving hybrid compounding of micrometer or even nanometer-scale carbon-silicate particles, and further obtaining highly dispersed carbon black-silicate hybrid particles, thereby achieving dispersion of hybrid particles in polymers such as rubber on a smaller scale; at the same time, it can remain unchanged in the existing carbon black production process and does not increase the environmental pressure of exhaust gas treatment.
[0011] Preferably, in step (1), the mass concentration of the carbon black structure inhibitor solution is 0.06-0.10%; the mass content of the carbon black structure inhibitor in the carbon black structure inhibitor solution is 0.04-0.08% of the mass of the crude oil; the flow rate of the carbon black structure inhibitor solution is 10-19 kg / h; the carbon black structure inhibitor in the carbon black structure inhibitor solution is selected from at least one of potassium carbonate and potassium formate.
[0012] Preferably, in step (1), the temperature of the combustion cracking reaction is 1800-2000°C.
[0013] Preferably, in step (2), the silicate is selected from at least one of white carbon black, kaolin and halloysite.
[0014] Preferably, in step (2), a pretreatment step is further included before the silicate and granulation water are mixed; the pretreatment method includes surface treatment or particle size refinement; and / or,
[0015] The surfactant used for the surface treatment is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane; the amount of the surfactant used is 0.5-1.0% of the mass of the silicate; and / or,
[0016] The particle size refinement method is pot milling for 2 to 5 hours.
[0017] Preferably, in step (2), the mass concentration of silicate in the silicate suspension is 10-30%; the flow rate of the silicate suspension during addition to the granulator is 800-1500 kg / h, and the temperature is 75-85°C.
[0018] Preferably, in step (2), the mass concentration of the adhesive solution is 5-20%; the mass content of the binder in the adhesive solution is 1-3% of the theoretical total mass of carbon black; the flow ratio of the adhesive solution to the silicate suspension is (2-6):1; the adhesive in the adhesive solution is selected from at least one of lignin, molasses, and maltose.
[0019] The present invention provides carbon black-silicate hybrid particles prepared by the preparation method described in the above technical solution.
[0020] The present invention also provides a rubber composite material comprising the carbon black-silicate hybrid particles described in the above technical solution.
[0021] Preferably, based on 100 phr of the raw rubber, the amount of the carbon black-silicate hybrid particles is 10 to 50 phr.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The existing method of introducing silicon-based particles at the carbon black production end will produce tail gas containing silicon elements, which will have a certain impact on tail gas treatment, emission, and even tail gas combustion heat transfer efficiency, etc., and there are certain environmental emission risks for the existing traditional carbon black production process. The preparation method provided by the present invention can maintain the existing carbon black production process without changing it and does not increase the environmental pressure of tail gas treatment.
[0024] The preparation method provided by the invention can obtain highly dispersed carbon black-silicate hybrid particles, which are used for preparing rubber materials and can improve the mechanical properties of the rubber materials.
[0025] The present invention introduces low-cost silicate particles, thereby increasing the output of hybrid carbon black and significantly reducing the cost of carbon black particles, thereby obtaining a high-quality and low-cost product. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 The equipment flow chart of the existing carbon black production process;
[0028] Among them, 1-reaction furnace; 2-main supply fan; 3-air preheater; 4-raw oil preheater; 5-quenching water pump; 6-raw oil pump; 7-main bag filter; 8-exhaust fan; 9-micron crusher; 10-air blower; 11-collecting cyclone separator; 12-return fan; 13-powdered carbon black storage tank; 14-wet granulator; 15-rotary dryer; 16-exhaust bag filter; 17-bucket elevator; 18-unqualified product storage tank; 19-screening machine; 20-magnetic separator; 21-screw conveyor; 22-product storage tank; 23-tank car;
[0029] Figure 2 TEM image of carbon black-white carbon black hybrid particles prepared in Example 1;
[0030] Figure 3 This is a transmission electron microscope dark field image of the carbon black-white carbon black hybrid particles prepared in Example 1;
[0031] Figure 4 Elemental composition analysis of the carbon black-silica hybrid particles prepared in Example 1;
[0032] Figure 5 TEM image of carbon black-white carbon black hybrid particles prepared in Example 2;
[0033] Figure 6 This is a transmission electron microscope dark field image of the carbon black-white carbon black hybrid particles prepared in Example 2;
[0034] Figure 7 Elemental composition analysis of the carbon black-silica hybrid particles prepared in Example 2. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] The embodiment of the present invention provides a method for preparing carbon black-silicate hybrid particles, comprising the following steps:
[0038] (1) feeding a carbon black structure inhibitor solution and crude oil into a reaction furnace for combustion and cracking reaction, and then cooling, filtering and crushing to obtain primary carbon black particles;
[0039] (2) mixing silicate and granulation water to obtain a silicate suspension; adding the obtained silicate suspension, the primary carbon black particles obtained in step (1) and the binder solution into a granulator for granulation to obtain the carbon black-silicate hybrid particles.
[0040] In a preferred embodiment, in step (1), the mass concentration of the carbon black structure inhibitor solution is 0.06-0.10%; the mass content of the carbon black structure inhibitor in the carbon black structure inhibitor solution is 0.04-0.08% of the mass of the crude oil; the flow rate of the carbon black structure inhibitor solution is 10-19 kg / h; the carbon black structure inhibitor in the carbon black structure inhibitor solution is selected from at least one of potassium carbonate and potassium formate. The present invention controls the concentration, dosage, flow rate and type of the carbon black structure inhibitor solution to produce primary carbon black particles with high structure, which is beneficial to obtain highly dispersed carbon black-silicate hybrid particles; changing the concentration, dosage, flow rate or type of the carbon black structure inhibitor solution will affect the structure of the primary carbon black particles, and ultimately affect the dispersibility of the carbon black-silicate hybrid particles.
[0041] In a preferred embodiment, in step (1), the temperature of the combustion cracking reaction is 1800-2000°C.
[0042] In a preferred embodiment, in step (2), the granulation water is deionized water.
[0043] In a preferred embodiment, in step (2), the silicate is selected from at least one of white carbon black, kaolin and halloysite. The present invention can significantly reduce the cost of carbon black particles while increasing the output of hybrid carbon black by introducing low-cost silicate particles, thereby obtaining a high-quality and low-cost product.
[0044] In a preferred embodiment, in step (2), a pretreatment step is further included before the silicate and granulation water are mixed; the pretreatment method includes surface treatment or particle size refinement. The present invention improves the compatibility of the silicate with carbon black by pretreating the silicate.
[0045] In a preferred embodiment, the surfactant used for the surface treatment is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane; the amount of the surfactant used is 0.5-1.0% of the mass of the silicate. Using a surfactant for surface treatment has the advantages of preventing particle agglomeration and improving material uniformity and stability.
[0046] In a preferred embodiment, the particle size refinement method is jar milling for 2 to 5 hours; the grinding balls used in the jar mill are zirconia balls; the mass ratio of the zirconia balls to the silicate is 5:1, and the mass ratio of the large, medium and small zirconia balls is 3:5:2; the speed of the jar mill is 500 to 700 rpm. The use of jar milling to refine the particle size of silicate has the advantage of simple operation.
[0047] In a preferred embodiment, in step (2), the mass concentration of silicate in the silicate suspension is 10-30%; the flow rate of the silicate suspension added to the granulator is 800-1500 kg / h, and the temperature is 75-85°C. The concentration and flow rate of the silicate suspension jointly determine the amount of silicate added during the granulation process, and further determine the mass proportion of silicate particles in the final obtained carbon black-silicate hybrid particles; if the concentration of the silicate suspension or the flow rate of the silicate suspension is too large, the content of silicate particles in the obtained carbon black-silicate hybrid particles is too high, which will cause the compatibility of the carbon black-silicate hybrid particles with the rubber matrix to decrease, and the reinforcing effect of the hybrid particles on the rubber matrix to be weakened; if the concentration of the silicate suspension or the flow rate of the silicate suspension is too small, the content of silicate particles in the obtained carbon black-silicate hybrid particles is too small, which will cause the hybrid particles to reinforce the ductility of the rubber to be not effectively exerted, and the fracture deformation of the material to be reduced.
[0048] In a preferred embodiment, in step (2), the mass concentration of the adhesive solution is 5-20%; the mass content of the binder in the adhesive solution is 1-3% of the theoretical total mass of carbon black; the flow ratio of the adhesive solution to the silicate suspension is (2-6):1; the adhesive in the adhesive solution is selected from at least one of lignin, molasses, and maltose. The concentration, dosage, flow rate, and type of the adhesive solution in the present invention will affect the structural parameters and porosity of the carbon black-silicate hybrid particles. Changing the concentration, dosage, flow rate, and type of the adhesive solution will change the particle size distribution, structure, and porosity of the carbon black-silicate hybrid particles, thereby affecting the dispersibility of the hybrid particles.
[0049] The present invention provides carbon black-silicate hybrid particles prepared by the preparation method described in the above technical solution.
[0050] In a preferred embodiment, the carbon black-silicate hybrid particles are composed of carbon black and silicate; the mass ratio of the carbon black to the silicate is (2-4):1.
[0051] The present invention also provides a rubber composite material comprising the carbon black-silicate hybrid particles described in the above technical solution.
[0052] In a preferred embodiment, based on 100 phr of the raw rubber, the amount of the carbon black-silicate hybrid particles is 10-50 phr.
[0053] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0054] Example 1
[0055] A method for preparing carbon black-silicate hybrid particles, the specific steps are as follows, using the existing carbon black production process, the equipment flow chart is shown in Figure 1 :
[0056] (1) preparing a potassium carbonate solution with a mass concentration of 0.07% by weight with 0.06% potassium carbonate (based on the total mass of the crude oil), and then feeding the potassium carbonate solution with the crude oil into a reaction furnace at a flow rate of 15 kg / h, performing a combustion cracking reaction at 1850° C. to generate carbon black flue gas, and cooling, filtering and crushing the generated carbon black flue gas to obtain primary carbon black particles;
[0057] (2) After grinding silica for 2 hours, disperse it in granulation water to obtain a silica suspension with a mass concentration of 20%, wherein the speed of the grinder is 500 rpm, the grinding balls used in the grinder are zirconium oxide balls, the mass ratio of zirconium oxide balls to silica is 5:1, and the mass ratio of large, medium and small zirconium oxide balls is 3:5:2; a lignin solution with a mass concentration of 15% is prepared, and the amount of lignin in the lignin solution accounts for 1.5% of the theoretical total mass of carbon black; the prepared lignin solution and the silica suspension are added to a granulator at a flow ratio of 4:1, wherein the flow rate of the silica suspension is 900 kg / h, and the temperature of the silica suspension is 75°C; after the granulation is completed, carbon black-silica (CB-SiO2) hybrid particles are obtained, which are dried and packaged to obtain finished products.
[0058] Figure 2 TEM image of carbon black-white carbon black hybrid particles prepared in Example 1, Figure 3 This is a dark field transmission electron microscope image of the carbon black-white carbon black hybrid particles prepared in Example 1. Figures 2-3 It can be seen that Example 1 achieves successful hybridization of CB and silica.
[0059] Figure 4 Elemental composition analysis of the carbon black-silica hybrid particles prepared in Example 1.
[0060] The element ratio analysis of the carbon black-white carbon black hybrid particles prepared in Example 1 is shown in Table 1.
[0061] Table 1 Element ratio analysis of CB-SiO2 hybrid particles prepared in Example 1
[0062] Element Name Mass fraction % C 70.22 Si 12.00 O 17.78
[0063] Depend on Figure 4 As can be seen from Table 1, in the carbon black-white carbon black hybrid particles CB-SiO2 prepared in Example 1, C:SiO2≈2.35:1.
[0064] Example 2
[0065] A method for preparing carbon black-silicate hybrid particles, the specific steps are as follows, using the existing carbon black production process, the equipment flow chart is shown in Figure 1 :
[0066] (1) 0.05% (based on the total weight of the crude oil) of potassium carbonate is prepared into a potassium carbonate solution with a mass concentration of 0.08%, and then the potassium carbonate solution is fed into a reaction furnace at a flow rate of 15 kg / h together with the crude oil, and a combustion and cracking reaction is performed at 1900° C. to generate carbon black flue gas, and the generated carbon black flue gas is cooled, filtered and crushed to obtain primary carbon black particles;
[0067] (2) dispersing the surface-treated silica with bis-[γ-(triethoxysilyl)propyl]tetrasulfide (the amount of bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 0.6% of the mass of silica) in granulation water to obtain a silica suspension with a mass concentration of 18%; preparing a lignin solution with a mass concentration of 10%, wherein the amount of lignin in the lignin solution accounts for 1.5% of the theoretical total mass of carbon black; respectively adding the prepared lignin solution and silica suspension into a granulator at a flow ratio of 3.5:1, wherein the flow rate of the silica suspension is 800 kg / h and the temperature of the silica suspension is 75°C; after the granulation is completed, carbon black-silica (CB-SiO2) hybrid particles are obtained, which are dried and packaged to obtain finished products.
[0068] Figure 5 TEM image of carbon black-white carbon black hybrid particles prepared in Example 2, Figure 6 This is a dark field transmission electron microscope image of the carbon black-white carbon black hybrid particles prepared in Example 2. Figures 5-6 It can be seen that Example 2 achieves successful hybridization of CB and silica.
[0069] Figure 7 Elemental composition analysis of the carbon black-silica hybrid particles prepared in Example 2.
[0070] The element ratio analysis of the carbon black-white carbon black hybrid particles prepared in Example 2 is shown in Table 2.
[0071] Table 2 Element ratio analysis of CB-SiO2 hybrid particles prepared in Example 2
[0072] Element Name Mass fraction % C 72.85 Si 10.52 O 16.63
[0073] Depend on Figure 7 As can be seen from Table 2, in the carbon black-white carbon black hybrid particles CB-SiO2 prepared in Example 2, C:SiO2≈2.70:1.
[0074] Example 3
[0075] A method for preparing carbon black-silicate hybrid particles, the specific steps are as follows, using the existing carbon black production process, the equipment flow chart is shown in Figure 1 :
[0076] (1) 0.08% (based on the total weight of the crude oil) of potassium formate is prepared into a potassium formate solution with a mass concentration of 0.10%, and then the potassium formate solution is fed into a reaction furnace together with the crude oil at a flow rate of 10 kg / h, and a combustion cracking reaction is carried out at 1950° C. to generate carbon black flue gas, and the generated carbon black flue gas is cooled, filtered and crushed to obtain primary carbon black particles;
[0077] (2) dispersing kaolin surface-treated with γ-aminopropyltriethoxysilane (the amount of γ-aminopropyltriethoxysilane is 0.8% of the mass of kaolin) in granulation water to obtain a kaolin suspension with a mass concentration of 25%; preparing a maltose solution with a mass concentration of 20%, wherein the amount of maltose in the maltose solution accounts for 2% of the theoretical total mass of carbon black; respectively adding the prepared maltose solution and kaolin suspension into a granulator at a flow ratio of 2:1, wherein the flow rate of the kaolin suspension is 850 kg / h and the temperature of the kaolin suspension is 85°C; after the granulation is completed, carbon black-kaolin (CB-Kaolin) hybrid particles are obtained, which are dried and packaged to obtain finished products.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that the potassium carbonate in step (1) is replaced by sodium carbonate, and the rest is the same as Example 1.
[0080] Comparative Example 2
[0081] The difference from Example 1 is that in step (1), 0.02% (based on the total mass of the crude oil) of potassium carbonate is used to prepare a potassium carbonate solution with a mass concentration of 0.07%, and the rest is the same as Example 1.
[0082] Comparative Example 3
[0083] The difference from Example 1 is that in step (1), 0.15% (based on the total mass of the crude oil) of potassium carbonate is used to prepare a potassium carbonate solution with a mass concentration of 0.07%, and the rest is the same as Example 1.
[0084] Comparative Example 4
[0085] The difference from Example 1 is that in step (1), 0.06% (based on the total mass of the crude oil) of potassium carbonate is used to prepare a potassium carbonate solution with a mass concentration of 0.20%, and the rest is the same as Example 1.
[0086] Comparative Example 5
[0087] The difference from Example 1 is that in step (1), the raw material oil is fed into the reactor at a flow rate of 25 kg / h, and the rest is the same as Example 1.
[0088] Comparative Example 6
[0089] The difference from Example 1 is that in step (2), white carbon black is directly dispersed in granulation water, that is, pot grinding is not performed. The rest is the same as Example 1.
[0090] Comparative Example 7
[0091] The difference from Example 1 is that in step (2), the amount of lignin in the lignin solution accounts for 0.5% of the theoretical total mass of carbon black, and the rest is the same as Example 1.
[0092] Comparative Example 8
[0093] The difference from Example 1 is that in step (2), the white carbon black is pot-milled for 2 hours and then dispersed in granulation water to obtain a white carbon black suspension with a mass concentration of 35%. The rest is the same as Example 1.
[0094] Application Example 1
[0095] The carbon black-white carbon black hybrid particles obtained in Example 1 were used to prepare a styrene-butadiene rubber (SBR) / carbon black composite material, and the specific steps were as follows:
[0096] (1) The styrene-butadiene rubber was plasticized on a two-roll mill for 2 minutes, and then zinc oxide and stearic acid were added in sequence and mixed for 2 minutes to make the additives evenly dispersed. During this period, a thin pass was made and a triangle bag was made;
[0097] (2) Add the carbon black-white carbon black hybrid particles obtained in Example 1 (with the same amount of pure carbon black as a reference) to the mixing rubber roll obtained in step (1), and mix for 6 minutes, during which the 3 / 4 knife is used 3 times on each side, 2 times for thin pass, and 2 times for triangular wrapping, so as to ensure that the particles are evenly dispersed in the rubber matrix;
[0098] (3) The mixing rubber roll obtained in step (2) was further added with accelerator CZ and accelerator DM, and mixed for 2 minutes, during which 3 / 4 knife was used twice on each side, thin pass once, and triangle wrap once;
[0099] (4) The mixing rubber roll obtained in step (3) is continuously added with sulfur as a vulcanizing agent and mixed for 2 minutes, during which 3 / 4 knife is used twice on each side, thin pass once, and triangle wrap once;
[0100] (5) Roll the mixed rubber obtained in step (4) on an open mixing mill with a roller spacing of 1.5 mm for 3 minutes, thinly pass through 5 times, and triangle wrap 5 times;
[0101] (6) The rubber mixture obtained in step (5) was left overnight and heated on a flat vulcanizing press at 160°C xt c90 Perform hot pressing and vulcanization molding to obtain a SBR / CB-SiO2 composite material;
[0102] Among them, based on the dosage of SBR being 100phr, the dosage of zinc oxide is 5phr, the dosage of stearic acid is 2phr, the dosage of accelerator CZ is 1.5phr, the dosage of accelerator DM is 0.5phr, the dosage of sulfur is 1.5phr, and the dosage of pure carbon black or carbon black-white carbon black hybrid particles is 10phr.
[0103] The mechanical properties of the composite material prepared in Application Example 1 were tested according to the test standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”, wherein the tensile rate was 500 mm / min. The results are shown in Table 3.
[0104] Table 3 Mechanical properties of SBR / CB-SiO2 composites prepared in Application Example 1
[0105]
[0106] As can be seen from Table 1, compared with the use of pure carbon black as the filling material, the styrene-butadiene rubber filled with CB-SiO2 hybrid particles exhibits higher tensile stress, tensile strength and elongation at break, which plays an obvious role in reinforcement and improving deformation rate, proving the advantages of the carbon black-silicate hybrid particles prepared by the present invention in carbon black-silicate composite filled styrene-butadiene rubber materials.
[0107] Application Example 2
[0108] The carbon black-white carbon black hybrid particles obtained in Example 2 were used to prepare a natural rubber (NR) / carbon black composite material, and the specific steps were as follows:
[0109] (1) The natural rubber was plasticized on a two-roll mill for 1.5 min, and then zinc oxide and stearic acid were added in sequence and mixed for 1.5 min to make the additives evenly dispersed. During this period, the rubber was thinly passed once and triangularly wrapped once;
[0110] (2) Add the carbon black-white carbon black hybrid particles obtained in Example 2 (with the same amount of pure carbon black added as a reference) to the mixing rubber roll obtained in step (1), and mix for 5 minutes. During this period, use a 3 / 4 knife for 3 times on each side, 2 times for thin pass, and 2 times for triangular wrapping to ensure that the particles are evenly dispersed in the rubber matrix;
[0111] (3) The mixing rubber roll obtained in step (2) was further added with accelerator TBBS and mixed for 2 minutes, during which 3 / 4 knife was used twice on each side, thin pass once, and triangle wrap once;
[0112] (4) The mixing rubber obtained in step (3) is rolled, sulfur is added as a vulcanizing agent, and mixing is performed for 1.5 min, during which 3 / 4 knife is used twice on each side, thin pass once, and triangle wrap once;
[0113] (5) Roll the mixed rubber obtained in step (4) on an open mixing mill with a roller spacing of 1.5 mm for 3 minutes, thinly pass through 5 times, and triangle wrap 5 times;
[0114] (6) the rubber mixture obtained in step (5) was left overnight, and hot-pressed and vulcanized on a flat vulcanizer at 143°C xtc90 to obtain a NR / CB-SiO2 composite material;
[0115] Wherein, based on the dosage of NR being 100 phr, the dosage of zinc oxide is 5 phr, the dosage of stearic acid is 2 phr, the dosage of accelerator TBBS is 1.5 phr, the dosage of sulfur is 2.0 phr, and the dosage of pure carbon black or carbon black-white carbon black hybrid particles is 50 phr.
[0116] The mechanical properties of the composite material prepared in Application Example 2 were tested according to the test standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”, wherein the tensile rate was 500 mm / min. The results are shown in Table 4.
[0117] Table 4 Mechanical properties of NR / CB-SiO2 composites prepared in Application Example 2
[0118]
[0119] As shown in Table 4, compared with the case of using pure carbon black as the filling material, the tensile stress value of the natural rubber filled with CB-SiO2 hybrid particles is slightly decreased, but the elongation at break and tensile strength values are significantly increased, which is beneficial to the tensile strain crystallization of the natural rubber itself under higher deformation and helps to improve the tensile strength of the material. This proves the advantages of the carbon black-silicate prepared by the present invention in filling natural rubber materials.
[0120] Application Example 3
[0121] The difference from Application Example 2 is that the carbon black-white carbon black hybrid particles obtained in Example 1 in step (2) are replaced by the carbon black-kaolin (CB-Kaolin) hybrid particles obtained in Example 3, and the rest are the same as Application Example 2.
[0122] Comparative Application Examples 1-8
[0123] The difference from Application Example 1 is that the carbon black-white carbon black hybrid particles obtained in Example 1 in step (2) are replaced by the carbon black-silicate hybrid particles obtained in Comparative Examples 1-8, respectively, and the rest are the same as Application Example 1.
[0124] The mechanical properties of the composite materials prepared in Application Example 3 and Comparative Application Examples 1-8 were tested according to the test standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”, wherein the tensile rate was 500 mm / min. The results are shown in Table 5.
[0125] Table 5 Mechanical properties of NR / CB-Kaolin composites prepared in Application Example 3 and SBR / CB-SiO2 composites prepared in Comparative Application Examples 1-8
[0126]
[0127] As shown in Table 5, the tensile stress, tensile strength and elongation at break of Example 3 are all higher than those of the natural rubber system filled with pure CB, indicating that CB-Kaolin achieves excellent reinforcement and relatively high cost performance. At the same time, from the analysis of the application data of Comparative Examples 1-8, the filling and reinforcing effect of the carbon black-white carbon black hybrid particles as fillers is improved to a certain extent compared with the pure carbon black system, and when the type, dosage, concentration and flow rate of the structural inhibitor, the pretreatment method of the silicate, the concentration of the silicate suspension and the dosage of the adhesive are changed, the tensile stress, tensile strength and elongation at break of the hybrid particle-filled SBR composite material are reduced to varying degrees, indicating that the reinforcement effect of the hybrid particles obtained by using high-structure carbon black particles and silicate suspensions with a concentration or mass within an appropriate range is more obvious.
[0128] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing carbon black-silicate hybrid particles, characterized in that: The following steps are involved: (1) feeding a carbon black structure inhibitor solution and crude oil into a reaction furnace for combustion and cracking reaction, and then cooling, filtering and crushing to obtain primary carbon black particles; (2) mixing silicate and granulation water to obtain a silicate suspension; adding the obtained silicate suspension, the primary carbon black particles obtained in step (1) and the binder solution into a granulator for granulation to obtain the carbon black-silicate hybrid particles.
2. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (1), the mass concentration of the carbon black structure inhibitor solution is 0.06-0.10%; the mass content of the carbon black structure inhibitor in the carbon black structure inhibitor solution is 0.04-0.08% of the mass of the crude oil; the flow rate of the carbon black structure inhibitor solution is 10-19 kg / h; the carbon black structure inhibitor in the carbon black structure inhibitor solution is selected from at least one of potassium carbonate and potassium formate.
3. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (1), the temperature of the combustion cracking reaction is 1800-2000°C.
4. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (2), the silicate is selected from at least one of white carbon black, kaolin and halloysite.
5. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (2), the silicate and granulation water are mixed before a pretreatment step is also included; The pretreatment method includes surface treatment or particle size refinement; and / or, The surfactant used for the surface treatment is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane; the amount of the surfactant used is 0.5-1.0% of the mass of the silicate; and / or, The particle size refinement method is pot milling for 2 to 5 hours.
6. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (2), the mass concentration of silicate in the silicate suspension is 10-30%; the flow rate of the silicate suspension during the addition to the granulator is 800-1500 kg / h, and the temperature is 75-85°C.
7. The method for preparing carbon black-silicate hybrid particles according to claim 1, characterized in that: In step (2), the mass concentration of the adhesive solution is 5-20%; the mass content of the binder in the adhesive solution is 1-3% of the theoretical total mass of carbon black; the flow ratio of the adhesive solution to the silicate suspension is (2-6):1; the adhesive in the adhesive solution is selected from at least one of lignin, molasses, and maltose.
8. Carbon black-silicate hybrid particles prepared by the preparation method according to any one of claims 1 to 7.
9. A rubber composite material comprising the carbon black-silicate hybrid particles according to claim 8.
10. The rubber composite material according to claim 9, characterized in that: Based on 100 phr of the raw rubber, the amount of the carbon black-silicate hybrid particles is 10 to 50 phr.
Citation Information
Patent Citations
Two-phase pyrolysis carbon black / white carbon black composite filler and preparation method thereof
CN104804479A
Preparation method of hydrotalcite-carbon black hybrid material as well as hydrotalcite-carbon black hybrid material / rubber composite material and application thereof
CN105001454A
Preparation method for modified carbon black-white carbon black double-phase particles
CN106554520A
Preparation method of modified white carbon black with chemical isolating structures
CN106883453A
Method for granulating waste tire pyrolysis carbon black and system for implementing same
CN109777157A